Proceedings of the 2006 Conference on Empirical Methods in Natural Language Processing - EMNLP '06 2006
DOI: 10.3115/1610075.1610091
|View full text |Cite
|
Sign up to set email alerts
|

Automatic classification of citation function

Abstract: Citation function is defined as the author's reason for citing a given paper (e.g. acknowledgement of the use of the cited method). The automatic recognition of the rhetorical function of citations in scientific text has many applications, from improvement of impact factor calculations to text summarisation and more informative citation indexers. We show that our annotation scheme for citation function is reliable, and present a supervised machine learning framework to automatically classify citation function,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
367
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 318 publications
(377 citation statements)
references
References 27 publications
8
367
1
1
Order By: Relevance
“…This noise is quite serious as a high incidence of perfunctory citations (40% or more) has been repeatedly observed in previous studies (Small, 1982). For example, Teufel, Siddharthan, and Tidhar (2006) found that only a fifth of references are essential for the citing papers, and Moravcsik and Murugesan (1975) noted that 40% references were perfunctory, frequently simply copied from other papers without ever having been read (Dubin, 2004).…”
Section: Research Questionsmentioning
confidence: 99%
“…This noise is quite serious as a high incidence of perfunctory citations (40% or more) has been repeatedly observed in previous studies (Small, 1982). For example, Teufel, Siddharthan, and Tidhar (2006) found that only a fifth of references are essential for the citing papers, and Moravcsik and Murugesan (1975) noted that 40% references were perfunctory, frequently simply copied from other papers without ever having been read (Dubin, 2004).…”
Section: Research Questionsmentioning
confidence: 99%
“…In recent years, the number of approaches for automatic classification of citations by key words or phrases has grown [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…A scientific article may be frequently cited, but it can be due to criticisms or mere acknowledgements, which distinguishes it from an article introducing an approach that is widely accepted and utilised. Several researchers can be mentioned in respect of qualitative citation based indicators in science (Moravcsik and Murugesan 1975;Swales 1986;Cano 1989;Teufel et al 2006;Athar and Teufel 2012). Cronin (1982) conducted a research of citation behaviours and noted that at the time there was not a universal approach in citation studies.…”
Section: Citation Analysismentioning
confidence: 99%
“…Application of qualitative citation based indicators often relies on linguistic discourse markers to generate conclusions about citations and citing behaviours. For example, citations can be classified according to sentiment polarities: confirmative or negative (Moravcsik and Murugesan 1975); positive, neutral or weak (Teufel et al 2006). Aspects of qualitative analysis of citations is relevant to our approach.…”
Section: Citation Analysismentioning
confidence: 99%
See 1 more Smart Citation